Bloqueio loco-regional no nervo infraorbitário equino com Tramadol 5% - (:unkn) unknown (Universidade Federal do Pampa, 2014)
The present study aimed to evaluate the potential local anesthetic tramadol 5% through the locoregional anesthesia in the infraorbital nerve horse. Reviewed by 9 crossbred horses (350 ± 60 kg) that after sedation and lock, underwent painful stimulations (PS). The animals received 1% acepromazine (0.05 mg / kg IV) and proceeded to shaving and applying anesthetic ointment, in the region of the foramen infraorbital. After 20 minutes, we proceeded to the local infiltration with tramadol 5% (5mL dose), the left infraorbital foramen (LIF). From long time (T0), every 10 minutes for 150 minutes were measured: respiratory rate (RR), heart rate (HR), rectal temperature (RT) and non-invasive blood pressure (NIBP). The PS were performed over a period of 30 "(thirty seconds), namely: manual needling in the gingival sulcus (teeth upper corner); wrinkling of the skin (in the cheek region) and narrowing of the upper lip, with hemostat Kelly, on the same side of the block. The latency period (LP) were recorded with PS performed each minute after T0, and the duration of block (DB) after end of the LP, with PS being made every 10 minutes until normal sensation returned. Was also collected blood samples to measure blood glucose. The negative control was performed with the infiltration of saline solution 0.9% (5mL dose), the right infraorbital foramen (RIF) in the same animal, getting the PS said, until the animal show discomfort. The data relating to HR, RR, NIBP, TR and glicemia were evaluated by ANOVA followed by Tukey post-test. For scores in relation to PS, the Kruskal-Wallis test followed by Dunn's test was used. There was local anesthesia with tramadol 5%, and the studied variables obtained oscillations, although within the physiological parameters of the species. The index was greater variation NIBP, but was due to the blockade prior reassurance. All animals showed ptosis (clinical finding) on the same side of the block, but at different intensities. The LP had an average duration of 5 minutes and the DB had maximum time of 140 minutes. It is concluded that tramadol 5%, the technique and the dose used, promoted perineural local anesthetic blockade and provided efficiently; Further studies are needed to verify the location toxicological potential, the dose / anesthetized area and local drug action mechanism.
Block in nerve locoregional infraorbitary equine with Tramadol 5%
Keywords: Bloqueio perineural; Analgesia; Tramadol; Equino; Perineural blockade; Analgesia; Tramadol; Equine; CNPQ::CIENCIAS DA SAUDE